Pelatihan Aplikasi CorelDRAW Siswa SMK Cakra Kusuma Desa Rejoagung Kecamatan Ngoro Kabupaten Jombang - Aisyah Indah Wulandari Putri; Yuniar, Eka (Bhinneka Publishing, 2022)
The purpose of this community service activity is: to provide training on graphic design applications using the CorelDRAW application where now a person is expected to have soft skills in any field. This training was held at the Cakra Kusuma Vocational School in Jombang Regency. It is hoped that this training will help Cakra Kusuma Vocational High School students with multimedia expertise get the supplies to enter the industrial world and be able to use the CorelDraw application. The method of community service is based on training, giving lectures directly on the tools in the CorelDraw application and also doing practical work on making stamp logos and certificates for an agency or company. The results of this training based on a questionnaire distributed to participants showed that 77% of students already knew what CorelDRAW was but to use graphic design applications they rarely or occasionally used it.